Increasing utilisation of skilled attendants at birth in sub-Saharan Africa: A systematic review of interventions. (August 2021) - Zuñiga, Julie A.; García, Alexandra; Kyololo, O'Brien M.; Hamilton-Solum, Patricia; Kabimba, Anne; Milimo, Benson; Abbyad, Christine W.; Reid, Davika D.; Chelagat, Dinah
Abstract: Background: Maternal mortality is a critical global public health concern, especially in low- and middle-income countries in sub-Saharan Africa. Although maternal mortality rates have declined by approximately 39% in sub-Saharan Africa over the last decade, maternal deaths during pregnancy and in childbirth remain high. Interventions to improve mothers' use of skilled birth attendants may decrease maternal mortality in sub-Saharan African countries. Objectives: This systematic literature review examines components of and evaluates the effectiveness of interventions to increase use of skilled birth attendants in sub-Saharan Africa. Methods: Guided by the PRISMA model for systematic reviews, the PubMed, Web of Science, and CIHNAL databases were searched for studies from years 2003 through June 2020. Results: The 28 articles included in this review reported on interventions incorporating community health workers, phone or text messages, implementation of community-level initiatives, free health care, cash incentives, an international multi-disciplinary volunteer team, and a group home for pregnant women, which improved use of skilled birth attendants to varying degrees. Only one study reported improved outcomes with the use of community health workers. All of the interventions using text messages increased hospital utilization for births. Conclusions: Interventions implemented in sub-Saharan Africa hold promise for improving maternal health. Multi-level interventions that involve community members and local leaders can help address the multi-faceted issue of poor maternal health outcomes and mortality. Interventions should focus on capacity building and on training and mentoring of formally-trained health care providers and community health workers in order to expand access.